Effect of Vitamin E on Endotoxin-Induced Disseminated Intravascular Coagulation in Rats - Yoshikawa, T; Furukawa, Y; Murakami, M; Watanabe, K; Kondo, M (Thrombosis and Haemostasis, 1982)
Experimental disseminated intravascular coagulation (DIC) can be induced by 4 hr sustained infusion of endotoxin in a dose of 100 mg/kg in rats. The experimental model of DIC in rats was used to study the preventive effect of vitamin E, α-tocopheryl acetate, against DIC. Before the infusion of endotoxin, 0.01, 0.1, 1.0 or 10.0 mg/kg/day of α-tocopheryl acetate was injected intraperitoneally for 4 successive days. The preventive effect against DIC was noted in all the parameters, such as fibrinogen and fibrin degradation products, fibrinogen level, prothrombin time, partial thromboplastin time, platelet count, and the number of renal glomeruli with fibrin thrombi, in rats treated with 1.0 or 10.0 mg/kg of α-tocopheryl acetate. From these results, it was shown that vitamin E, α-tocopheryl acetate, inhibited endotoxin-induced experimental DIC in rats.
Keywords: DIC; Endotoxin; α-tocopheryl acetate; Rat